The Risk of a Shod and Unshod Horse Kick to Create Orbital Fractures in Equine Cadaveric Skulls - Joss, Rahel; Baschnagel, Fabio; Ohlerth, Stefani; Piskoty, Gabor; Fürst, Anton; Bischofberger, Andrea S. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to compare the potential of an unshod and shod hoof to cause an orbital fracture in the event of a kick.Materials and Methods Thirty-four equine cadaveric orbitae were exposed to a steel or horn impactor in a dropping test set-up. An impactor velocity of 7 m/s was used for both materials. Testing was repeated on the same orbit at a velocity of 10 m/s with the horn impactor if no damage occurred. A high-speed camera was used to analyse the impact process. Physical parameters (peak force and impact duration) were calculated based on quantitative video-tracking. Computed tomographic (CT) scans were generated and fracture configurations described.Results At 7 m/s, the fracture probability was lower for horn (23.5%) than for steel impactors (70.6%, p = 0.015). On CT-images, damage of the frontal, temporal, zygomatic and lacrimal bones was detected. Furthermore, the orbital socket (17.2%), the supraorbital foramen (34.5%) and the temporomandibular joint (58.6%) were involved. The frequency of affected orbital bones was not significantly different between fractures generated by steel and horn impactors, but the fracture severity was subjectively greater when fractures were generated by steel impactors.Clinical Significance The orbital fracture probability was significantly higher when a kick of a shod versus unshod horse was simulated. This indicates that keeping horses unshod would decrease the injury risk of neighbouring horses when considering group housing systems.
Keywords: horse kick; computed tomography; shoeing material; temporomandibular joint; orbital fracture